Application of Bloom’s Taxonomy in the Process of Teaching Biological Disciplines in Higher Education (Journal of Educational Sciences, 2020)
Currently, higher education in Kazakhstan is undergoing a period of unprecedented change. The main driver of these changes is the influence of innovative technologies in the educational process. Teachers and scientists believe that traditional forms of learning are outdated, to capture the attention of students, it is necessary to introduce innovative teaching technologies. Today, many higher education institutions in the process of learning are moving to the use of innovative technologies. Since innovative technologies have several advantages: stimulate active learning; give quick feedback; establish teacher contact with students forms «unconventional» thinking among students; encourage student collaboration; encourage a variety of learning methods. From the above, we can understand that innovative technologies have radically changed the old paradigm of «teaching and learning». In the new learning example, the role of the student is more important than teachers. The main goal of innovative technologies is to prepare a person for life in an ever-changing and evolving society. The researchers analyzed an innovative technology - Bloom’s taxonomy in teaching the discipline «Human and Animal Physiology». The analysis of the seminar and theoretical materials are presented in accordance with Bloom’s taxonomy, in which tasks are classified into 6 levels: the first level is “Knowledge”, the second level is “Understanding”, the third level is “Application”, the fourth level is “Analysis”, the fifth level is “Synthesis”, sixth level – “Assessment”. A questionnaire survey was conducted among students at the Department of Biophysics and Biomedicine, Faculty of Biology and Biotechnology, AlFarabi Kazakh National University in order to identify their attitude to innovative teaching technologies, in which 24% of respondents showed the greatest interest in Bloom’s taxonomy. And in order to emphasize that each level of Bloom’s taxonomy is built on the basis of previous levels, a model of this innovative technology was developed. Key words: educational process, innovative technology, Bloom’s taxonomy, assessment criteria, analysis, teaching methods.